DOP78 Comparative study of the effectiveness of vedolizumab versus ustekinumab after anti-TNF failure (VERSUS-CD). (21st January 2022) - García, M J; Rivero, M; Fernández-Clotet, A; de Francisco, R; Sicilia, B; Mesonero, F; de Castro, M L; Casanova, M J; Bertoletti, F; García Alonso, F J; López García, A; Julián, B; et al.
Abstract: Background: Main aim: To evaluate the retention rate of ustekinumab compared to vedolizumab in Crohn's disease patients who failed anti-TNF therapy in clinical practice. Secondary aims: To compare the short-term and long-term effectiveness, and the safety of both treatments. Methods: Crohn's disease patients who had received either vedolizumab or ustekinumab after failure or intolerance to anti-TNF agents from ENEIDA registry were included. ENEIDA is a prospectively maintained database promoted by GETECCU. A total of 755 patients from 30 centres were included at time of data extraction. Clinical activity was classified based on Harvey-Bradshaw index both at short (during induction) and in the long-term. Kaplan-Meier curves, Cox regression models, inverse probability weighting and propensity matching score analyses were performed to compare both drugs and to identify predictive factors of treatment effectiveness and durability. Results: 755 patients were included (195 in the vedolizumab cohort and 560 in the ustekinumab cohort). After a median of 20 months (IQR 7.4–30) of follow-up, the survival rate for ustekinumab therapy was higher than vedolizumab (Figure 1). The propensity matching score verified the differences between both therapies. The short-term proportion of patients on clinical remission, steroid-free remission and clinical response was also superior in the ustekinumab cohort (Figure 2). In the long-term, significant differences were observed 2 years after the beginning of the treatments, although no differences in clinical response and remission rates were detected in patients who achieved clinical response at week 16 between both cohorts. Vedolizumab was discontinued in 142 patients and ustekinumab in 185, mainly due to primary non-response (52% in the vedolizumab and 58% in the ustekinumab cohort) and loss of response (34% and 25%, respectively) despite the fact that 35% of the patients required intensification. The predictive factors associated to the discontinuation of the therapy are described in table 1. Adverse events were observed, overall, in 12% of the patients, without differences between both groups (Table 2). Following the discontinuation of the treatment with vedolizumab/ustekinumab, other biologic agents were prescribed in 56% of the patients, and 27% underwent surgery. Conclusion: In clinical practice, a relatively high proportion of Crohn's disease patients who received ustekinumab or vedolizumab for anti-TNF failure, maintained these drugs in the medium-long term, although ustekinumab retention rate was higher in comparison with vedolizumab.